Standards of online teaching & learning in Pakistan - DR. Mamoona Muhammad Anwar, (Pakistan Journal of Medical & Health Sciences, 2022)
Due to the pandemic COVID-19 both teachers & learners have to move to e-learning/online system from physical classrooms which put both to a challenging situation. The major difficulty students faced was the lack of interaction as most of the teachers were convenient with audio interaction, further active participation & comprehension was quite poor as in physical classrooms .Online assessments such as open book tests made academic dishonesty scenarios quite easy for students1. Communication is the backbone of any teaching–learning process; a study at undergraduate level at the University of Malak and emphasize communication/language as a barrier in e-learning as if teachers voice is not comprehensive enough due to the poor connectivity issues in remote areas or if their accent is not understandable for learners or the use of complex terms & lastly the absence of non-verbal communication such as body language2. E-learning has its own benefits as well as drawbacks. We can overcome most of the barriers faced by both learners & teachers by conducting webinars, teacher training programs as well as by the availability of smooth internet connection both for learners & teachers. Government can also play a major role by providing free laptops & connectivity devices to all those who can’t afford3. A study conducted on medical undergraduate students of Dow International University Karachi that emphasize the impact of online learning of medical students. All the clinical rotations needed to be cancelled due to this pandemic that affects negatively on the clinical skills & on the development of student-patient interaction/relationship. Students can improve their online learning satisfaction by learning technology & learners can become more productive with professional faculty training programs4. A few students find online learning as robotic teaching because of the less/no eye contact & physical interaction among learners & teachers